Kompatibilitas dan Efektifitas Fungi Mikorisa Arbuskula (FMA) terhadap Kacang Komak (Dolichos lablab L) - Sidqi Zaed Z.M.; Gita Pawana; Slamet Supriyadi (Universitas Trunojoyo Madura, 2008)
Besides, low nutrient availability the problem in dry land of Madura is the conflict of land use for food crops and forage production. Overcoming the problem a program that unite agriculture and husbandry activities is needed. The objective of this research was to find out the most compatible and effective isolate of AMF on hyachinth bean (Dolichos lablab L) as a forage legume. The AMF which were Gigaspora sp, Glomus sp, Glomus manihotis, Acaulospora sp dan Entrophosopra sp were planted beneath the bean seeds in polybag and the plants were managed in a green house in optimal condition. The result showed that among isolates of arbuscular micorrhizal fungi, Gigaspora sp. greatly influenced growth and yield of biomass of hyachinth bean (Dolichos lablab L) indicating dependency of the plant to the fungus. It is concluded that Gigaspora sp is the most compatible isolate for legume of hyachinth bean (Dolichos lablab L).